PRARANCANGAN PABRIK TOLUENEDIAMINE DARI DINITROTOLUENE DENGAN KAPASITAS 50.000 TON/ TAHUN - , DIAN PURNAMI HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toluene diamine is an organic compound that is widely used in polyurethane industry as a main raw material. Polyurethane used as a raw material for spandex, glue, plastic, and tire. There is no toluenediamine industry established in Indonesia, it can be a chance to develop this industry. The plant is designed to operate for 330 days/year with a toluene diamine production capacity of 50,000 tons/year. The main raw material required are 74,665.9 tons/year of 99% dinitro toluene and 4,908.4 tons/year hydrogen. The process used is the Tolochieme Patent with nickel Raney catalyst. In general, toluenediamine manufacturing process stages are : (i) mixing dinitro toluene and methanol, (ii) hydrogenation of dinitro toluene with nickel Raney catalyst, (iii) purification of toluene diamine product, (iv) using prilling tower to make toluenediamine form. As a support, utility plant unit supplies 808.63 kVA electricity. The plant will be established in Kendal Kaliwungu Semarang. Thatâs region close to PT Samator as a supplier of hydrogen gas and also near to the sea, it will be good for the transportation of raw material, product, and the supply of sea water for utility plant. Calculation of economic evaluation results is fixed capital required equal to $12,275,983.5 and Rp141.743.390.798,7 and working capital equal to $55,592,373.8 and Rp25.745.524.135,5. At 100% production rate, obtained ROI before tax of 34,8%, ROI after tax of 17.4%, POT before tax of 2.3 years, POT after tax of 3.9 years, with BEP at 52.4%, SDP at 37.3%, and 24.8 % for DCFRR. Based on consideration of the economic evaluation results, this toluene diamine plant with capacity 50,000 tons / year worth to be studied further.